2022
DOI: 10.1071/fp21288
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in hydrogen sulfide-induced adventitious rooting in tomato (

Abstract: Nitric oxide (NO) and hydrogen sulfide (H2S) are signalling molecules that regulate adventitious rooting in plants. However, little is known about the cross-talk between NO and H2S during adventitious rooting. Tomato (Solanum lycopersicum L.) explants were used to investigate the roles of and relationships between NO and H2S during rooting. Effects of the NO donor sodium nitroprusside (SNP) and the H2S donor sodium hydrosulfide (NaHS) on adventitious rooting were dose-dependent, and the greatest biological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In this study, we found that DEGs were expressed at four different stages of root development and were enriched in various pathways (Figure 2). During the rooting process, the activities of antioxidant enzymes may enhance the plant's ability to withstand abiotic stress and contribute to the formation of ARs [35][36][37]. Therefore, researching the root development mechanisms of genes related to antioxidant enzymes will help address the question of the low propagation coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that DEGs were expressed at four different stages of root development and were enriched in various pathways (Figure 2). During the rooting process, the activities of antioxidant enzymes may enhance the plant's ability to withstand abiotic stress and contribute to the formation of ARs [35][36][37]. Therefore, researching the root development mechanisms of genes related to antioxidant enzymes will help address the question of the low propagation coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…The increased degradation of HY5 resulted in decreased expression of the ABI5 gene, thereby enhancing seed germination under heat stress [ 68 ]. In another study, the combinatorial effect of NO and H 2 S signaling regulated the adventitious rooting in tomato plants by activating the expression of auxin-related genes (ARF4 and ARF16) and cell cycle-related genes (CYCD3, CYCA3, and CDKA1) [ 69 ]. Exogenous application of NaHS leads to the activation of transcription and activity of L-DES1 that stimulates the H 2 S biosynthesis, which in turn activates the germination of Arabidopsis seeds [ 70 ].…”
Section: Crosstalk Between Ros/rns/rss In Plant Defensementioning
confidence: 99%
“…Nitric oxide (NO) has been implicated as an essential signaling molecule in plants. Numerous studies have discovered that NO plays an essential role in the regulation of plant growth and development including seed germination ( Ren et al., 2020 ), root growth and development ( Pagnussat et al., 2002 ; Sun et al., 2019 ; Liu et al, 2022a ), pollen tube germination ( Prado et al., 2004 ) and fruit senescence ( Zuccarelli et al., 2021 ). The increasing evidence indicates that, NO function in plant stress response.…”
Section: Introductionmentioning
confidence: 99%